2004
DOI: 10.1074/jbc.m403485200
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Handoff between Bacteriophage T7 DNA Primase and T7 DNA Polymerase Initiates DNA Synthesis

Abstract: The T7 DNA primase synthesizes tetraribonucleotides that prime DNA synthesis by T7 DNA polymerase but only on the condition that the primase stabilizes the primed DNA template in the polymerase active site. We used NMR experiments and alanine scanning mutagenesis to identify residues in the zinc binding domain of T7 primase that engage the primed DNA template to initiate DNA synthesis by T7 DNA polymerase. These residues cover one face of the zinc binding domain and include a number of aromatic amino acids tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 58 publications
(93 reference statements)
5
60
1
1
Order By: Relevance
“…The enhanced use of primers by full-length gp4 suggests that the polymerase engages gp4 through contacts with the primase and helicase domains or the helicase domain efficiently tethers the primase domain to DNA. The requirement for a physical interaction between gp4 and T7 DNA polymerase to promote primer extension (14,15) is underscored by the inability of other polymerases, such as T4 DNA polymerase or the Klenow fragment of E. coli DNA polymerase I, to extend primers synthesized by gp4 (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced use of primers by full-length gp4 suggests that the polymerase engages gp4 through contacts with the primase and helicase domains or the helicase domain efficiently tethers the primase domain to DNA. The requirement for a physical interaction between gp4 and T7 DNA polymerase to promote primer extension (14,15) is underscored by the inability of other polymerases, such as T4 DNA polymerase or the Klenow fragment of E. coli DNA polymerase I, to extend primers synthesized by gp4 (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, gp4⌬primase binds the ssDNA 3-fold less tightly (K d of 411 Ϯ 53 nM) and binds 30% of the oligonucleotide at the highest protein concentration. The 3-fold poorer binding of gp4⌬primase to ssDNA is likely due to the fact that gp4⌬primase does not contain the RPD that alone can bind ssDNA (31). It was proposed earlier that the primase facilitates loading of gp4 onto ssDNA (32).…”
Section: Physical Interactions Between the Dna Helicase Domain Of Gp4mentioning
confidence: 99%
“…In a previous study, the replacement of Trp-42 with alanine in the ZBD decreased de novo synthesis of tetraribonucleotide and partially reduced its utilization as primers by DNA polymerase (24). However, replacement of tryptophan with alanine is too drastic to meaningfully deduce the structural roles of the tryptophan from the properties of the altered ZBD.…”
Section: Discussionmentioning
confidence: 87%
“…1): Trp-42 in the ZBD, Trp-69 and Trp-97 in the N-terminal subdomain of the RPD, and Trp-147 and Trp-255 in the C-terminal TOPRIM fold of the RPD. A previous study showed that the replacement of Trp-42 with alanine in the ZBD greatly decreases tetraribonucleotide synthesis and partially reduces their utilization as primers by T7 DNA polymerase (24). In another study, the substitution of non-aromatic residues for Trp-69 significantly impairs the ability of gp4 to synthesize primers and deliver them to DNA polymerase (25).…”
mentioning
confidence: 99%